High-performance flexible surface-enhanced Raman scattering substrate based on the particle-in-multiscale 3D structure - Zhou, Yaning; Yao, Haizi; Liu, Chundong; Chen, Mengyu; Zhang, Chao; Liu, Mei; Wang, Jian; Fujun Zhang; Yu, Jing; Man, Baoyuan; Sun, Qianqian (Nanophotonics (Berlin, Germany), 2021)
Recently, multiscale three-dimensional (3D) structures consisting of micrometer-scale structure and nanometer-scale structure have received some attention from scientists in the field of surface-enhanced Raman scattering (SERS). In this work, micrometer-scale grating structure and nanometer-scale zinc oxide nano spikes (ZnO NSs) structure are successfully introduced into the SERS substrate with silver nanoparticles (Ag NPs) as the surface plasmon. The optimized particle-in-multiscale 3D substrate (PDMS/grating/ZnO NSs/Ag NPs) presents high sensitivity with an ultralow limit of detection of 1 × 10 M and a high enhancement factor of 7.0 × 10 for Rhodamine 6G (R6G) as the probe molecule. It benefits from the electromagnetic field enhancement from the excellent optical capture capability of grating/ZnO NSs structure and abundant electromagnetic hot spots. The quantitative analysis ability of the SERS substrate can be indicated from the good linear correlation between the logarithmic Raman intensity and the molecular concentration. At the same time, this SERS substrate exhibits excellent homogeneity and reproducibility, which have low relative standard deviations (4.43%) of the Raman intensities at 613 cm peaks for R6G as the probe molecule. In addition, this SERS substrate can realize detection of Raman signal due to its excellent light transmission and flexibility. The particle-in-multiscale 3D structure as SERS substrate exhibits the vast potential in practical applicability for qualitatively and quantitatively chemical and biomedical analysis.